Accurate identification and detection of occlusal/smooth early caries using thermal-wave radar imaging (TWRI) technique under low temperature rising condition. (January 2022) - Wang, Fei; Wu, Lianjun; Wang, Xiaochun; Liang, Yuming; Liu, Junyan; Chen, Mingjun; Wang, Yang
Highlights: Thermal-wave radar imaging (TWRI) technique was utilized to detect dental caries at an early stage in this present study. The relationship between laser power intensity and dental surface temperature rise has been investigated. The experimental results illustrated that TWRI approach can be used as an effective method for early caries diagnosis. Abstract: Dental caries is a worldwide disease, which will cause adverse effects if it is not treated in time. To accurate detect the early caries, a dental caries recognized approach based on infrared thermal diffusion, titled thermal-wave radar imaging (TWRI) technique was utilized to detect dental caries at an early stage in this present study. One-dimensional (1D) thermal-wave model under linear frequency modulation (or -chirp) thermal flux was built and analyzed the chirp thermal-wave diffusion behavior. In addition, simulated caries environment in vitro was designed and proposed for the treatment of artificial dental caries. Four intact tooth tissues were demineralized with this etching agent for different time on the dental occlusal surface. For the safety of the laser application in clinical trials, the relationship between laser power intensity and dental surface temperature rise has been investigated. When the laser power intensity was controlled within 23.3 W under the irradiation area is 2 mm × 2 mm, the surface temperature rise of dental specimen can be dominated within 5 °C. The comparison experiment between TWRI and lock-in thermography was investigated, and TWRI phase represents a high signal-to noise ratio to the early caries. μCT was utilized to 3D tomography for the dental specimen to obtain the actual caries inside the specimen. The experimental results illustrated that TWRI approach can be used as an effective method for early caries diagnosis.